2009
DOI: 10.1007/s11259-009-9216-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three commercially available prescription diet regimens on short-term post-prandial serum glucose and insulin concentrations in healthy cats

Abstract: Dietary therapy is an important treatment component for diabetes mellitus (DM). In this study, the impact of three different commercially available diet regiments (1 general use and 2 aimed for treating obesity and DM) on short-term post-prandial serum glucose and insulin concentrations of five healthy cats to better understand what impact each of these diets may have for diabetic cats. The diet regiments used in this study were as follows: C/D dry (General Use- Low protein, High fat, High carbohydrate, and Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 27 publications
3
16
0
Order By: Relevance
“…The lower blood glucose concentrations in our cats fed the lower carbohydrate diets is consistent with previous findings, however, others have not reported differences, largely because of the methodology used, or the difference in carbohydrate content was not as great . It was not surprising that we found no differences in glucose tolerance test results between the diets, because the glucose tolerance test is performed after a 24‐hour fast, and the glucose load is the same for all cats.…”
Section: Discussionsupporting
confidence: 91%
“…The lower blood glucose concentrations in our cats fed the lower carbohydrate diets is consistent with previous findings, however, others have not reported differences, largely because of the methodology used, or the difference in carbohydrate content was not as great . It was not surprising that we found no differences in glucose tolerance test results between the diets, because the glucose tolerance test is performed after a 24‐hour fast, and the glucose load is the same for all cats.…”
Section: Discussionsupporting
confidence: 91%
“…Our results corroborate a previous study reporting that healthy cats fed a diet for 4 weeks with approximately 50% of energy from carbohydrates, demonstrated a significantly higher mean glucose concentration and glucose AUC as compared with cats fed diets with 25% of energy from carbohydrates [11]. Interestingly, the M/D and Diabetic diets also resulted in a postprandial glucose level lower than the preprandial level, in which is consistent with our results from a previous study where healthy cats were used [28].…”
Section: Discussionsupporting
confidence: 92%
“…However, information on the effects of the use of commercially available prescription diets to manage feline obesity is scarce and thus far includes only two studies that have investigated the effects of these diets on glucose and insulin concentrations in cats [8,26]. Furthermore, our previous study demonstrated that commercially available diabetic prescription diets affect postprandial glucose and insulin concentrations in nonobese healthy cats [28]; however, no study has investigated the effects in obese cats.…”
mentioning
confidence: 99%
“…However, such hyperglycaemia has the same effect on some omnivore species (Imamura et al., 1988), and the level of starch present in extruded dry‐type diets does not consistently produce an extraordinary hyperglycaemia in cats compared to other species (Kienzle, 2004; de‐Oliveira et al., 2008). Also, the plasma insulin response in cats to ‘high’ dietary carbohydrate is not consistently found to be greater than the response to a ‘high’ dietary protein (Rand et al., 2003; Mori et al., 2009).…”
Section: Introductionmentioning
confidence: 99%